Asymmetric dihydroxylation route towards the synthesis of (R)-clorprenaline hydrochloride - Pandey, Rajesh Kumar; Upadhyay, Rajesh Kumar; Kumar, Pradeep (Arkivoc, 2006)
An efficient asymmetric synthesis of enantiomerically pure (R)-clorprenaline hydrochloride is described using Sharpless asymmetric dihydroxylation as the key step.